Penyitaan Harta untuk Nafkah Anak: Rekonstruksi Hukum Berbasis Maqāṣid al-Syarī‘ah: A Maqāṣid-Based Legal Reconstruction - Zakiul Fuady Muhammad Daud; Kuntari Madchaini; Khairuddin Khairuddin; Husni Mubarrak (Al-Ulum, 2026)
This study examines post-divorce child support in Indonesian Islamic law and positive law, focusing on the legal basis for confiscating ex-husbands’ assets and proposing a maqāṣid-based enforcement model. Using a normative-juridical method with statutory, conceptual, and case approaches, the study analyzes laws, court decisions, and fiqh literature through the maqāṣid framework. Findings show that although both systems obligate fathers to provide support, enforcement remains weak, with many decisions unexecuted, reflecting a lack of operational norms and resulting in structural injustice. From a maqāṣid perspective, asset confiscation is a legitimate and necessary instrument aligned with the protection of offspring (ḥifẓ al-nasl) and property (ḥifẓ al-māl). The study underscores the need to transform Islamic family law toward an operational, enforcement-oriented approach and recommends strengthening legislation and proactive judicial practices to ensure effective fulfillment of children’s rights.